Características do acidente vascular cerebral associado á doença de Chagas - Fidel Castro Alves de Meira (2016)
Chagas disease (CD) is an infectious disease caused by the protozoan parasite Trypanosoma cruzi. It is estimated that 5.7 million people are infected by this parasite in Latin America. Chagasic cardiomyopathy is the main clinical form of CD and it affects 20 to 30% of infected individuals. Structural cardiac changes (i.e. apical aneurism) and cardiac rhythm disturbances (i.e. atrial fibrillation) may occur in this form of the disease. Both conditions are related to embolic phenomena like stroke. Other proposed mechanisms for the relation between CD and stroke are brain microvasculopathy and arterial wall stiffness. This study was based in the review of medical records from patients admitted to Hospital Risoleta Tolentino Neves due to acute ischemic stroke (AIS). Data regarding demographics, cardiovascular risk factors (including CD diagnosis), medications, laboratory results, time for discharge, treatment with venous alteplase and in-hospital mortality were recorded. AIS patients with CD were compared to non-CD AIS patients (in a 1:4 proportion). This study was evaluated and approved by the local ethics committee. Five hundred fifty eight patients were included in this study, being 490 with AIS diagnosis. Twenty two had CD. For comparison, 88 patients with non-CD related stroke were selected. CD and non-CD groups were similar regarding gender, age and hospital stay. Cardioembolic stroke was the main stroke subtype in the CD group (77.3%; p<0.001) while stroke of undetermined etiology predominated in non-CD group. Hypertension was statically more prevalent in non-CD group (81.8%; p=0.023), while cardiopathy (68.2; p<0.001) and previous stroke or transient ischemic attack (50.0%; p=0.016) were more prevalent in CD group. This group also had a significant difference for the use of oral anticoagulation (22.7%; p=0.008). Endovenous alteplase use were similar in both groups. Cervical artery ultrasound findings did not show statistical difference between the two groups. Echocardiography data analysis showed a significantly greater proportion of myocardial hypokinesia, myocardial akinesia, left ventricular thrombus, apical 11 aneurism and lower left ventricular ejection fraction among CD patients. Hospital mortality was similar between the two groups. In conclusion, patients with CD and stroke show clinical differences, mainly related to heart problems, when compared to patients with ischemic stroke without CD.